(untitled) (International Journal of Current Engineering and Technology, 2014)
With the ever increasing number of cloud service providers, rising competition, and the growing popularity of cloud, it is extremely important for cloud providers to improve their services by improving the operational cost (response time and the processing time of requests). Since cloud computing is primarily driven by its cost effectiveness and as the scheduling of priority processes for profit, particularly in Inter-Cloud systems, has not been much focused, we propose a scheduling method using power of two choices with priority to address the service request scheduling problem with priority. The algorithm is based on power of two choices randomized load balancing in Inter-Cloud scheduling and has a priority feature. We will demonstrate that the giving priority to some processes by user for which he or she seeks better response time than average response time of the processes, using power of two choices with priority algorithm has a better response time for priority process. By providing better response time to priority processes Cloud service providers can take higher charges comparing with normal processes and thus increases their profit without much affecting the response time of the normal processes.